2010
DOI: 10.1007/s10059-010-0027-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Fat Due to Estrogen Deficiency Induces Bone Loss by Elevating Monocyte Chemoattractant Protein-1 (MCP-1) Production

Abstract: Ovariectomy (OVX)-induced estrogen withdrawal resulted in both bone loss and an increase in fat. We observed elevated osteoclast (OC) formation by bone marrow-derived macrophages treated with medium conditioned by fats from OVX mice, but not from sham-operated mice. Fats from OVX mice expressed and secreted higher levels of monocyte chemoattractant protein-1 (MCP-1) than those from sham-operated mice. Increased fat resulting from estrogen deficiency is thus responsible for bone loss due to enhanced OC formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…The lack of MCP-1 attenuated the influx of blood CD11c cells, which were significantly elevated by OVX, thus partly explaining the increase of CD11c cells in AT of OVX mice. Previously we have demonstrated that OVX increased serum MCP-1 [20]. OVX also resulted in increase of M-CSF compared with sham surgery, whereas the absence of MCP-1 reduced it.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The lack of MCP-1 attenuated the influx of blood CD11c cells, which were significantly elevated by OVX, thus partly explaining the increase of CD11c cells in AT of OVX mice. Previously we have demonstrated that OVX increased serum MCP-1 [20]. OVX also resulted in increase of M-CSF compared with sham surgery, whereas the absence of MCP-1 reduced it.…”
Section: Discussionmentioning
confidence: 77%
“…In previous studies, we demonstrated that OVX increases serum MCP-1 level [20]. To investigate whether MCP-1 contributes to OVX-induced metabolic dysfunction, we analyzed MCP-1-knockout (KO) mice, compared with wild type (WT) mice.…”
Section: Resultsmentioning
confidence: 99%
“…The average daily intake of food was not different between SHAM and OVX groups, indicating that lipid accumulation in OVX mice was not a result of hyperphagy. But probably a result of alterations in fatty acid metabolism, as an activated hepatic fatty acid synthesis and impaired fatty acid oxidation (Kumagai et al 1993;Sanyal et al 2001;Kim et al 2010). Body weight gain and adiposity were reduced with both the treatments and the levels of glucose, total cholesterol, LDL-cholesterol and VLDLcholesterol were decreased in OVX mice treated with UDCA, or HRT.…”
Section: Discussionmentioning
confidence: 99%
“…Observed in our study, the concentrations of TRAP significantly increased from week 8 to week 12, indicating that the osteoclastogenesis might be activated by corticosteroids. MCP-1 also plays a very important role in activating and aggregating the monocytes/macrophages [37]. Moreover, steroid-induced osteonecrosis arose from the aberrant immune response and the imbalance of bone metabolism.…”
Section: Discussionmentioning
confidence: 99%